2015
DOI: 10.1002/pds.3803
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy among pharmacy visitors in the Netherlands

Abstract: Approximately half of the pharmacy visitors in this study had limited health literacy skills. These individuals experienced more difficulties understanding drug label instructions. These findings emphasize the need to identify patients with limited health literacy skills, as these patients might be at increased risk for drug-related problems caused by misunderstanding of information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…This is in line with findings reported in the literature (Chew et al 2004; Koster et al 2015; van der Heide et al 2015). However, the predictive power of our model was not very high, suggesting that healthcare professionals cannot solely depend on age, education level and non-Western background to identify patients at risk of having limited health literacy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with findings reported in the literature (Chew et al 2004; Koster et al 2015; van der Heide et al 2015). However, the predictive power of our model was not very high, suggesting that healthcare professionals cannot solely depend on age, education level and non-Western background to identify patients at risk of having limited health literacy.…”
Section: Discussionsupporting
confidence: 93%
“…Low health literacy has previously been associated with poorer surgical outcomes and misunderstanding of information (Koster et al 2015). Inadequate understanding of information or instructions may also have negative consequences for the hospital in terms of delayed or cancelled surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, Koster et al confirmed these findings in an immigrant population with poor knowledge of Dutch and found that the instruction to use prescriptions as needed and auxiliary labels are problematic: 40% of label instructions were understood correctly . In another study, they confirmed the association between low health literacy and problems with understanding prescription labels …”
Section: Introductionmentioning
confidence: 83%
“…In addition, the interviews were guided by a structured interview protocol; therefore, we assume this limitation will not affect our findings. We frequently work with pharmacy interns and successfully used students for data collection in our previous studies . It should be noted that the social desirability bias may have influenced the respondents and that in daily clinical practice their actual behaviour to attend for patients with limited health literacy patients may be different.…”
Section: Discussionmentioning
confidence: 99%
“…An important reason for incorrect use of medicines might be patients’ misunderstanding of – both written and verbal – information or instructions given by healthcare providers . Previous studies have shown that patients often experience difficulties in understanding medication related information, such as medicine information leaflets and drug labels …”
Section: Introductionmentioning
confidence: 99%